The Dopamine Receptor D4 Gene (DRD4) and Financial Risk-Taking: Stimulating and Instrumental Risk-Taking Propensity and Motivation to Engage in Investment Activity - Muda, Rafał; Kicia, Mariusz; Michalak-Wojnowska, Małgorzata; Ginszt, Michał; Filip, Agata; Gawda, Piotr; Majcher, Piotr (Frontiers in Behavioral Neuroscience, 2018)
The Dopamine receptor D4 gene (DRD4) has been previously linked to financial risk-taking propensity. Past works demonstrated that individuals with a specific variant of the DRD4 gene (7R+) are more risk-seeking than people without it (7R-). The most prominent explanation for this effect is the fact that 7R+ individuals are less sensitive to dopamine and thus seek more stimulation to generate “normal” dopaminergic activity and feel pleasure. However, results about this relationship have not been conclusive, and some revealed a lack of the relationship. In the current work, we tested if those unclear results might be explained by the motivation that underlies the risk-taking activity; i.e., if people take risks to feel excitement or if they take risk to obtain a specific goal. In our study we tested the differences in risk-taking between 7R+ and 7R- among people who are experienced in financial risk-taking (113 investors) and non-experienced financial decision makers (104 non-investors). We measured risk-taking propensity with the Holt-Laury test and the Stimulating-Instrumental Risk Inventory. Moreover, we asked investors about their motivations for engaging in investment activity. Our study is the next one to report a lack of differences in risk-taking between 7R+ and 7R- individuals. As well, our results did not indicate any differences between the 7R+ and 7R- investors in motivation to engage in investment activity. We only observed that risk-taking propensity was higher among investors than non-investors and this was noticed for all measures. More research is needed to better understand the genetic foundations of risk-taking, which could answer the question about the substantial variation in the domain of risky financial decisions.